Snakes and Ladders Game Education in Choosing Healthy Snacks for Elementary School Students - Herawati, Cucu; Endayani, Heni; Indragiri, Suzana; Wahyuni, Nuniek Tri; Supriatin, Supriatin; Kristanti, Iin (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Snacks for school children whose health is not guaranteed can cause food poisoning. The minimum level of knowledge of elementary school children about the dangers of the snacks they consume. One of the efforts to prevent health problems due to food in school children is educational activities about food sanitation hygiene. The purpose of this community service is to provide education on the game of snakes and ladders in choosing healthy snacks for elementary school students, so that it is hoped that children's knowledge will increase and behave healthily in choosing snacks.The target of implementing the intervention was grade IV students. The method of implementing the intervention is by observing and educating students with the snakes and ladders game method with the theme of healthy snacks. Primary data was obtained through observation and question and answer before education was carried out through the game of snakes and ladders. The secondary data includes a description of the school, the number of students. Stages or educational procedures for snakes and ladders game: stage 1 (opening), stage 2 (division of groups) and stage 3 (game atmosphere), namely game rules such as snakes and ladders games in general. This community service activity was carried out for class IV students, totaling 25 students. The activity was carried out on 29 August -16 September 2022. The results of observations on student behavior in choosing snacks showed that many chose brightly colored snacks, snacks that were sold openly and used newspaper wrappers. The intervention method for community service activities uses the snakes and ladders game method with the theme of healthy snacks. Here students are invited to play while learning. It is better for school children to get used to having breakfast before school and bringing supplies and getting used to washing hands using soap and running water, especially before eating and after eating.